A new oviraptorid (Dinosauria: Theropoda) from the Upper Cretaceous of southern China - Wang, Shuo; Sun, Chengkai; Sullivan, Corwin; Xu, Xing (Zootaxa, 2013)
This paper describes a new oviraptorid dinosaur taxon, Ganzhousaurus nankangensis gen. et sp. nov., based on a specimen collected from the Upper Cretaceous Nanxiong Formation of Nankang County, Ganzhou City, Jiangxi Province, southern China. This new taxon is distinguishable from other oviraptorids based on the following unique combination of primitive and derived features: relatively shallow dentary; absence of fossa or pneumatopore on lateral surface of dentary; weakly downturned anterior mandibular end; shallow depression immediately surrounding anterior margin of external mandibular fenestra; external mandibular fenestra subdivided by anterior process of surangular; dentary posteroventral process slight-ly twisted and positioned on mandibular ventrolateral surface; shallow longitudinal groove along medial surface of den-tary posteroventral process; angular anterior process wider transversely than deep dorsoventrally; sharp groove along ventrolateral surface of angular anterior process; ventral border of external mandibular fenestra formed mainly by angular; ventral flange along distal half of metatarsal II; and arctometatarsal condition absent. Phylogenetic analysis places Gan-zhousaurus nankangensis gen. et sp. nov. in the clade Oviraptoridae, together with Oviraptor, Citipati, Rinchenia and the unnamed Zamyn Khondt oviraptorid.